SINONIM UTSUKUSHII DAN KIREI - Gilang Anugrah Manusakerti; Arza Aibonotika; Intan Suri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is about a synonym of utsukushii and kirei. Utsukushii and kirei have similar meaning in Japanese, that is ‘beautiful’. In sentences these words have some distinctions depend on the context of sentences. The purpose of this research is to describes semantically the meaning of utsukushii and kirei. The data was collected from Japanese dictionary, Japanese books, and commercial messages in Japanese.Key Words: Meaning, synonym, semantics